Recent reforms in Spanish housing markets: an evaluation using a DSGE model - Mora-Sanguinetti, Juan S.; Rubio, Margarita (Elsevier, 2014)
After a long academic debate, Spain finally repealed in 2012 the deduction for home purchase. The abrogation took effect in 2013. In parallel, the VAT for the purchase of new housing was increased after a short period in which it had a reduced rate. The aim of this paper is to assess the macroeconomic effects of these two relevant housing market reforms. In order to do that, we use a dynamic stochastic general equilibrium (DSGE) model calibrated to capture the key ratios of the Spanish economy. The model includes a housing market, covering both the rental market side and the property market side and credit-constrained agents. We find that these measures drive down housing prices and have a negative impact on output and employment in the construction sector. However, in the long run, this last effect is offset by the benefits of a reduction in distortionary taxes.